2004
DOI: 10.1152/physiolgenomics.00165.2003
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling protein 2 and 3 in marsupials: identification, phylogeny, and gene expression in response to cold and fasting in Antechinus flavipes

Abstract: We searched for the presence of uncoupling protein genes so far unknown in marsupials and monotremes and identified uncoupling protein 2 (UCP2) and UCP3 full-length cDNAs in libraries constructed from the marsupials Antechinus flavipes and Sminthopsis macroura. Marsupial UCP2 is 89-90% identical to rodent UCP2, whereas UCP3 exhibits 80% identity to mouse UCP3. A phylogenetic tree including all known UCPs positions the novel marsupial UCP2 and UCP3 at the base of the mammalian orthologs. In the 5'-untranslated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 59 publications
2
39
1
Order By: Relevance
“…It has been previously reported that UCP3 is not upregulated in rodent skeletal muscle following cold acclimation (Boss et al, 1997(Boss et al, , 1998), but Toyomizu et al (2002) reported that UCP3 expression is induced in the skeletal muscle of cold-exposed chickens. More recently, UCP3 was not induced in Antechinus flavipes, a similar sized Australian marsupial, although the period of cold exposure was short (Jastroch et al, 2004). Thus although equivocal, a role for UCP3 in muscle thermogenesis may be better elucidated in organisms in which skeletal muscle plays a primary role in thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that UCP3 is not upregulated in rodent skeletal muscle following cold acclimation (Boss et al, 1997(Boss et al, , 1998), but Toyomizu et al (2002) reported that UCP3 expression is induced in the skeletal muscle of cold-exposed chickens. More recently, UCP3 was not induced in Antechinus flavipes, a similar sized Australian marsupial, although the period of cold exposure was short (Jastroch et al, 2004). Thus although equivocal, a role for UCP3 in muscle thermogenesis may be better elucidated in organisms in which skeletal muscle plays a primary role in thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously (Jastroch et al, 2004), physical gene maps of verified UCP loci were scaled based on assemblies of the Ensembl Genome Browser. Genes located up-and downstream of UCP genes in these loci were blasted against human, mouse and zebrafish genomes for the highest score.…”
Section: Comparative Genomicsmentioning
confidence: 99%
“…Total RNA was isolated using TRIzol (Gibco BRL), quantified and subjected to northern blot analysis as described previously (Jastroch et al, 2004). The membranes were hybridized using Xenopus laevis 251 bp UCP1 and 550 bp UCP2 cDNA probes derived with Xenopus tropicalis gene specific primers (UCP1: forward 5Ј-GGCTCC AGAGACAGATGAGCTTCGC-3Ј, reverse 5Ј-GGC -TATGGT TT TATAGGCGTCCATAGTGCC-3Ј; UCP2: forward 5Ј-GGTTCGG TTCCAAGCTCAGGCC-3Ј, reverse 5Ј-ATGGC -ACA GT TGATGGCGCTGG-3Ј).…”
Section: Rna Isolation and Northern Blot Analysismentioning
confidence: 99%
“…Homologues of UCP1 have been identified in various mammalian tissues Damon et al, 2000;Nakatani et al, 2002;Jastroch et al, 2004), but also in birds Vianna et al, 2001;Talbot et al, 2004), plants (Laloi et al, 1997;Maia et al, 1998;HourtonCabassa et al, 2004), protists (Jarmuszkiewicz et al, 1999) and fungi (Jarmuszkiewicz et al, 2000), thus suggesting a more central role for the UCP family in metabolism. The specific nature of the UCP isoforms as proton channels, however, is less well established.…”
Section: Introductionmentioning
confidence: 99%